Assessment of heterogeneity of soil and water characteristics of kala oya estuary from river mouth to river fall - Panchalingam, M. (university of Jaffna, 2020)
Assessment of the heterogeneity of soil and water quality characteristics from river mouth to river fall of Kala Oya estuary on North-Western coast of Sri Lanka for a period of four months from March to June 2017 was carried out. The objective is to determine the primary soil characteristics including Total Organic Matter Content (TOC), Moisture content, Soil pH while water quality characteristics such as pH, Dissolved oxygen, temperature and electrical conductivity in three locations at three different distances [river mouth (0m), mid estuary (691m), river fall (1880m)]. Although there is no significant difference in TOC in 3 sites (p<0.05, one way ANOVA). Slight variations were recorded with the highest value of (2.76+0.27) at river mouth. according to principal component analysis (PCA), river mouth was indicated with higher bulk density, soil pH, and electrical conductivity whereas the higher organic content and moisture content were characterized by the mid of the estuary. Thus there were variation in the physico-chemical parameters in water and soil across the river mouth to river fall in Kala Oya estuary.
Keywords: Heterogeneity; Physio-chemical parameters; Kala oya estuary